Pengaruh Ketepatan Pengalokasian Pajak Dan Tax Morale Terhadap Tax Evasion - Mardani, Mardani; Rizal, Anis Syamsu (JURNAL ADMINISTRASI KANTOR; Vol 11 No 1 (2023): Jurnal Administrasi Kantor (Juni 2023)DO - 10.51211/jak.v11i1.2238, 2023)
Tax is one of the main sources of state revenue and expenditure (APBN) for the Indonesian people. Taxes are used to support the Indonesian economy because almost 85% of the Indonesian Government's APBN comes from the tax sector. Taxes are used to fund the welfare and prosperity of people's lives. Most of Indonesia's state income comes from tax revenues. The government must form a State Revenue and Expenditure Budget (APBN) to control the national economy, the government in carrying out its duties uses one method, namely by imposing levies in the form of taxes on the public. This study aims to determine the effect of Accuracy of Tax Allocation and Tax Morale on Tax Evasion. This type of research is quantitative research. The population of this study is individual taxpayers who are registered at the Depok Cimanggis primary tax service office. Sampling using the Slovin formula. The number of samples distributed was 115. The data collection method in this study was a questionnaire. Data analysis techniques used are descriptive statistics, data quality testing, classic assumption testing, hypothesis testing. The partial results of the study show that (1) there is a significant influence between the accuracy of allocating taxes on tax evasion, (2) there is a significant influence between tax morale and tax evasion. While simultaneously the Accuracy of Tax Allocation and Tax Morale have a significant influence on Tax evasion   Keywords : Accuracy of Tax Allocation, Tax Morale, Tax Evasion.